Ni/Ni12P5 Heterostructure Decorated on Multi‐channel Carbonized Wood Frameworks for Efficient Hydrogen Evolution. Issue 48 (21st December 2022) - Wang, Zhiqiang; Pan, Yichen; Yang, Caixia; Zhang, Jiancheng; Li, Caicai; Sun, Qingfeng
Abstract: For exploiting high‐efficiency and stable non‐noble metal hydrogen evolution reaction (HER) electrocatalysts, rationally design and optimizing the electrode structures are extremely essential. Herein, inspired by the abundant pores and highly ordered multi‐channel structures of natural wood, a typical electrode with Ni/Ni12 P5 heterostructure embedded in the multi‐channel carbonized wood frameworks (Ni/Ni12 P5 /CW) was designed and fabricated. The open micro‐channel structure and electrical conductivity of carbonized wood (CW) facilitates electron transfer, electrolyte penetration, and gas diffusion. Meanwhile, formation of the Ni/Ni12 P5 heterostructure is beneficial to improve the activity of pristine nickel phosphide. As expected, the Ni/Ni12 P5 /CW electrode exhibited excellent HER catalytic activity, which merely needed overpotentials of 86, 138 and 173 mV to drive 10, 50 and 100 mA cm −2 in alkaline media, respectively. In addition, it showed superior durability with no significant degradation for more than 60 h of continuous operation at different current densities. This work will enlighten the development and utilization of wood‐based materials for application in electrocatalysis. Abstract : A typical electrode with Ni/Ni12 P5 rooted in the multi‐channel carbonized wood frameworks (Ni/Ni12 P5 /CW) was designed and fabricated. Formation of the Ni/Ni12 P5 heterostructure was beneficial to improve the activity of pristine nickel phosphide, while the well‐aligned multi‐channel structures of the electrode facilitated to accelerate the catalytic reaction kinetics, and thereby excellent HER catalytic activity was obtained.